Assessment of Principals’ Personnel Management Practices in Public and Private Senior Secondary Schools in Benue State, Nigeria - ATTE, Priscillia Temitope; OJO, Idowu Christopher (International Journal of Educational Management, 2021)
This study assessed principals’ personnel management practices in private and public senior secondary schools in Benue State, Nigeria. The study was carried out to find out how principals manage staff discipline, appraisal and recruitment. The descriptive survey design was adopted for the research. The research study discovered that: principals do not fully implement personnel management practices (staff discipline, staff appraisal and staff recruitment) in both public and private secondary schools in Benue State, Nigeria. Recommendations made from the study included that: Principals should encourage disciplinary acts among teachers, they should ensure that the teachers are well acquainted with the code of ethics to enable them comply strictly with it, appraisal reports on staff should be considered during promotions and appointments.